“REFERENTIAL ERRORS AND THEIR CAUSES IN THE CONTEXT OF TWO LANGUAGES” (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article explores referential errors and their underlying causes in English and Uzbek language contexts. Referential errors occur when language users fail to accurately identify or maintain the intended referent in discourse. These mistakes can lead to ambiguity, misunderstanding, or communication breakdown. The paper compares how such errors emerge due to linguistic, syntactic, and pragmatic differences in the two languages. It also examines the influence of cognitive and cultural factors on referential accuracy. By analyzing real examples from both languages, the study aims to highlight the specific features that contribute to referential errors and suggest strategies for improving communicative effectiveness and translation accuracy.